2023
DOI: 10.3389/fimmu.2023.1110001
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive tract-organ axes

Abstract: The female reproductive tract (FRT) and remote/versatile organs in the body share bidirectional communication. In this review, we discuss the framework of the “FRT-organ axes.” Each axis, namely, the vagina-gut axis, uterus-gut axis, ovary-gut axis, vagina-bladder axis, vagina-oral axis, uterus-oral axis, vagina-brain axis, uterus-brain axis, and vagina-joint axis, is comprehensively discussed separately. Each axis could be involved in the pathogenesis of not only gynecological diseases but also diseases occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 196 publications
0
13
0
Order By: Relevance
“…This suggests that the oral cavity and vagina share a common microbial community and that there is also a reciprocal exchange of related microbial communities. The salivary microbiota of participants with bacterial vaginosis (BV) was more diverse than that of BV-negative participants [ 36 ], and Prevotella intermedia and Porphyromonas endodontalis were enriched in the subgingival gingival microbiota of BV-infected women compared to women without BV, which indicates the presence of a vagino–oral axis [ 37 ]. Moreover, Porphyromonas and Prevotella have been proven to have carcinogenic potential via several different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the oral cavity and vagina share a common microbial community and that there is also a reciprocal exchange of related microbial communities. The salivary microbiota of participants with bacterial vaginosis (BV) was more diverse than that of BV-negative participants [ 36 ], and Prevotella intermedia and Porphyromonas endodontalis were enriched in the subgingival gingival microbiota of BV-infected women compared to women without BV, which indicates the presence of a vagino–oral axis [ 37 ]. Moreover, Porphyromonas and Prevotella have been proven to have carcinogenic potential via several different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal microbiome transformations along the cervical carcinogenesis route have been characterized, but the associated impacts on the oral niche remain underexplored. This study revealed that the oral cavity contains a significantly greater number of bacterial species than does the vagina and revealed extensive bidirectional sharing of microbial communities between the vaginal and oral cavities through an emerging vagino–oral axis [ 37 ]. This study provides insight into the microbial community shared between the oral and vaginal parts of the human body, as well as the exchange of related microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Excess short-chain fatty acids may be a possible cause of cervicovaginal inflammation, according to an in vitro investigation ( Delgado-Diaz et al, 2020 ). Therefore, vaginal microecological dysregulation brought on by the flow of short-chain fatty acids from the gut to the vagina may cause menstruation abnormalities ( Takada et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…When circulating estrogen reaches the distal epithelium of the vagina, it modifies the physiological traits of the cells that line the vagina, including the generation of mucus and glycogen. Since glycogen can be a vital source of energy for Lactobacilli , increased glycogen promotes Lactobacillus dominance in the vagina ( Witkin, 2018 ; Linhares et al, 2019 ; Takada et al, 2023 ). Therefore, the number of Lactobacillus in the vaginal microbiota can be influenced by the number of bacteria in the gut microbiota that metabolize estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of the gut microbiota has been linked to an increased risk of vaginal infections, including BV and VVC (Tuddenham et al 2019 ; Han et al 2021 ). Furthermore, emerging evidence suggests that the transmission of microbial communities between the gut and vagina may occur through various routes, including the bloodstream, mucosal surfaces, and shared anatomical pathways (Takada et al 2023 ) .…”
Section: Gut Connection: Exploring the Influence Of Vaginal Microbiom...mentioning
confidence: 99%